2003
DOI: 10.1046/j.1462-2920.2003.00535.x
|View full text |Cite
|
Sign up to set email alerts
|

Stable isotope probing of rRNA and DNA reveals a dynamic methylotroph community and trophic interactions with fungi and protozoa in oxic rice field soil

Abstract: Stable isotope probing (SIP) is a novel technique to characterize structure and in situ function of active microbial populations, which is based on the incorporation of 13C-labelled substrates into nucleic acids. Here, we have traced methylotrophic members of a rice field soil microbial community, which became active upon continuous addition of 13C-methanol (< 22 mM) as studied in microcosms. By combining rRNA- and DNA-based SIP, as well as domain-specific real-time PCR detection of templates in fractions of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
189
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(197 citation statements)
references
References 54 publications
7
189
0
1
Order By: Relevance
“…Methanol-utilizing methylotrophs can be metabolically stimulated by adding millimolar concentrations of methanol to aerated and flooded soil (Radajewski et al, 2002;Lueders et al, 2004). However, the methylotrophs responsible for in situ methanol consumption are unresolved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Methanol-utilizing methylotrophs can be metabolically stimulated by adding millimolar concentrations of methanol to aerated and flooded soil (Radajewski et al, 2002;Lueders et al, 2004). However, the methylotrophs responsible for in situ methanol consumption are unresolved.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge of the in situ diversity of methanol-utilizing methylotrophs in soils is limited despite the fact that many soil-derived methanol-utilizing methylotrophs have been isolated or detected by molecular analyses by employing high and likely not in situ-relevant methanol concentrations (Radajewski et al, 2002;Lueders et al, 2004;Lidstrom, 2006;Kolb, 2009a). Methanolutilizing Burkholderiaceae, Beijerinkiaceae and Bradyrhizobiacea occur in aerated soils (Radajewski et al, 2002).…”
Section: Diversity Of Soil Methylotrophsmentioning
confidence: 99%
“…Lueders et al (2004) combined RNAand DNA-SIP to monitor activation and temporal dynamics of methylotrophs in soil. The authors suggested that after 6 days of incubation with labelled substrate, RNA-SIP recovered the initially active bacteria, whereas a specific enriched methylotroph was identified after 42 days of incubation Ecology of methanotrophs in a landfill soil M HĂ©ry et al using DNA-SIP.…”
Section: Ecology Of Methanotrophs In a Landfill Soilmentioning
confidence: 99%
“…Application of the PhyloChip (Affymetrix, Santa Clara, CA, USA) to cathode biofilm communities offered a higherresolution analysis of the microbial community composition than previously reported methods Wrighton et al, 2008), and thus the possibility of uncovering more diversity than was previously observed in these systems. We restricted our analysis to the active members of the communities by monitoring 16S rRNA (rather than the 16S rRNA gene), which is a more responsive biomarker and a better surrogate for microbial activity in bacterial communities (Lueders et al, 2004). Populations identified as dominant by PhyloChip were verified with fluorescence in situ hybridization (FISH) analysis.…”
Section: Introductionmentioning
confidence: 99%